Effects of organic-inorganic complex fertilizer on the growth and physiological characteristics of ‘Qi-Nan’ agarwood from Aquilaria sinensis (Lour.) - Jingyue Huang; Yunlin Fu; Zhu Yu; Xueting Li; Siyu Zheng; Fenyong Tang; Penglian Wei (PLoS ONE, 2025)
This paper is to study the effects of different levels of fertilization on the growth, physiological characteristic of ‘Qi-Nan’ agarwood seedlings. The experiment was conducted under potted conditions using a single factor experiment. Organic-inorganic complex fertilizer was used as the basal fertilizers, and 7 fertilizer gradients ranging from 0 g/plant to 23 g/plant were set up. The result showed that: (1) within a certain range, with the increase of organic-inorganic complex fertilizer application, the growth and physiological activity of ‘Qi-Nan’ had an incremental effect, but this effect would be inhibited when the fertilizer application was too high. (2) After fertilization, the contents of free proline (FP) and malondialdehyde (MDA) decreased, while the contents of osmotic regulatory substances and chlorophyll increased. (3) The correlation analysis showed that seedling height and ground diameter of ‘Qi-Nan’ seedlings were significantly positively correlated with soluble sugar content, peroxidase activity and chlorophyll content. (4) Membership function analysis showed that organic-inorganic complex fertilizer had a significant effect on the growth of ‘Qi-Nan’ seedlings, and the optimal fertilizer level of single application of organic-inorganic complex fertilizer was 7-11g/plant. Therefore, the optimal application level of organic-inorganic complex fertilizer for the seedling cultivation of ‘Qi-Nan’ was 7g/ plant.